Calling and conscience: Paul as an example - Malan, Gert (Verbum et ecclesia, 2024)
Paul’s calling presents a conundrum to which many have proposed varied solutions. Not trying to solve the conundrum in toto , this study investigates the existential dynamics of Paul’s calling as narrated to the Galatians within the context of their apostasy. The model used is Heidegger’s understanding of conscience as a call towards authenticity and away from inauthenticity. Rhetorical analysis assists in identifying Paul’s new understanding of authenticity, by analysing the propositio , especially its expositio , which contains soteriological peculiar existential first-person singular expressions. Paul’s preaching of his gospel and his letter to the Galatians are in turn also to them, a call to authenticity and away from inauthenticity. His preaching thus resembles the phenomenological idea of conscience. Thus, Paul’s gospel cannot be separated from his calling. Both are about the same understanding of authenticity. It is at the same time a new self-understanding: to have been crucified with Christ and therefore Christ living in him and the faithful (Gl 2:19-20). This is a concise formula of soteriology as symbolised in baptism. Such calling is never completed: it remains a dynamic process, a tension and movement between authenticity and inauthenticity. This is reflected in the Galatian apostasy and Paul’s letter calling them back to authenticity. The study underlines the crucial importance of soteriology for kerygma and baptism, but especially for understanding a person’s call to faith or ministry. Intradisciplinary and/or interdisciplinary implications: The model is suitable for studying the religious phenomenon of calling in religious texts and in life.